WORD FORMATION PROCEES OF THE GIANTS’ NAMES IN THE BFG - A CHILDREN BOOK WRITTEN BY ROAL DAHL - Elisna Huan (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
The aim of this research was to find out the types of word formation in the names of the giants; the fictional characters in children's book entitled The BFG written by Roald Dahl. This research was designed as descriptive qualitative research.To investigate the language phenomenon, the writer employed Yule's theoretical framework regarding the word-formation process. There are 10 types of word-formation processes proposed by Yule (2010), such as coinage, borrowing, compounding, blending, conversion, acronym, derivation, back-formation, clipping, and multiple processes. But apparently, in creating names for the giants characters in the story, Dahl only used 3 types of word formation, they are an acronym, compounding, and multiple processes.